A malha valorativo-discursiva da atual extrema direita brasileira : ecos nazifascistas e vestígios da política do “nós” versus “eles” - Paschoal, Cristiano Sandim (2021)
Considering that language – as a social practice – organizes, represents, and conceives the concrete reality of a society, this study is based on the hypothesis that the current Brazilian far-right political discourse contains Nazifascism ideological values. Supported by theoretical and methodological postulates of the Bakhtin Circle, whose understanding is that meanings from past centuries can be reborn, re-signified and acquire new semantic-axiological tones, the study comprises the following questions guiding: a) For what reason is it possible to affirm the presence of Nazifascism ideology in the current Brazilian far-right political discourse? b) How are Nazifascist verbal-axiological resonances projected in the far-right discourse? c) According to the dialogic discourse theory, every discursive idea is ideological and, consequently, reflects and refracts a certain social reality. Therefore, what socio-discursive consequences, caused by dialogic existence, can be observed in the Brazilian society nowadays? From these questions, this research main objective is to investigate how Nazifascist ideologies are reverberated by the Brazilian far-right discourse, forming its own evaluative-discursive network, marked by the discursive idea of “us” versus “them”. As secondary objectives, this research aims to: a) Analyze how Nazifascist ideologies are reverberated in the speech of exponents in the current Brazilian far-right; b) Examine verbal elements that comprise the enunciations, as well as the non-verbal and extraverbal elements that constitute their meanings (social atmosphere, the body language of the speakers, verbal-visual elements, etc.); c) Investigate the consequences of Nazifascist ideologies present in the statements pronounced by Jair Messias Bolsonaro and his ministerial support towards the Brazilian social horizon, suggesting the possibility arising from a phenomenon of reflection and refraction; d) Investigate how the analyzed statements indicate a discursive network filled by Nazi-fascist ideologies, resulting in a regimental policy marked by “us” versus “them” that divide society, turning “them” into a national enemy archetype. Five statements pronounced by members of the current Brazilian Federal government were selected for analysis. Regarding the methodology, the analytical path for each statement was elaborated in two moments: the first moment involved the examination of the Nazifascist ideologies that emerge from the statements; the second moment speculated a phenomenal possibility of reflection and refraction from the meanings investigated regarding the Brazilian socio-discursive horizon. The analysis showed that the statements presented the following semantic-axiological epicenters: the construction of a political enemy, the imaginary construction of a mythical past, anti-intellectualism, anti-Semitism and religiosity, from which religious and racial prejudice emerge. All these meanings, dialogically intertwined, indicate the existence of a singular evaluative-discursive print within the current Brazilian government, which, in the political spectrum of the far-right, is characterized, among many things, by an axiological vision marked by Nazifascist echoes that aim the stratification of society into “us” versus “them”, conceiving “them” as a national enemy.